2020
DOI: 10.1021/acs.joc.9b02839
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Syntheses of Spiro[indoline-3,4′-pyridin]-2-yl Carbamates via AgOTf/Ph3P-Catalyzed Tandem Cyclizations of Tryptamine-Ynesulfonamides

Abstract: Spiro­[indoline-3,4′-piperidine] is a significant structural scaffold in numerous polycyclic indole alkaloids with a variety of bioactivities. In this study, a synthetic strategy was developed to access spiro­[indoline-3,4′-pyridin]-2-yl carbamate via an AgOTf/PPh3-catalyzed tandem cyclization of tryptamine-ynesulfonamides. The unique feature of this strategy is the efficient intermolecular capturing of the in situ generated spiroindoleninium intermediates with carbamates, leading to the diastereoselective syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…4,5 Likewise, the addition of carbon centred nucleophiles to the C2 of indole was explored by the Ohno, Huang, and Liu groups. 6–8…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Likewise, the addition of carbon centred nucleophiles to the C2 of indole was explored by the Ohno, Huang, and Liu groups. 6–8…”
Section: Introductionmentioning
confidence: 99%
“…The importance of tryptamine-ynamides as versatile building blocks in organic synthesis, especially in the construction of indoline scaffolds, has been established by many elegant pioneering works due to the development of synthetic methods of tryptamine-ynamide. 7 Most cases reported to date relied on the electron-donating ability of nitrogen, leading to the regioselective addition of nucleophiles to the α-carbons of ynamides and the formation of spiro[indole-3,3′-pyrrolidine]. 7 a , b , d , e , h Ye and our group reported the opposite regioselectivity via a umpolung-type additions of indole to ynamides controlled by the chelating group of nitrogen under the catalysis of metal such as copper and silver salts, resulting in formation of azepino[4,5- b ]indole derivatives.…”
mentioning
confidence: 99%
“…As a result, there have been a few reports on the synthesis of spiroindolines using tryptamine-derived ynamides (Scheme ). However, during the synthesis of spiroindolines from tryptamine-derived ynamides, a carbon bond is formed at C-2 via rapid Wagner–Meerwein rearrangement. Previous research has reported the requirement of intramolecular traps with an appropriate nucleophile to prevent this.…”
mentioning
confidence: 99%